Association between weight-adjusted-waist index and retinopathy among American adults: a cross-sectional study and mediation analysis - Li, Junmeng; Yin, Qianshuo; Hao, Jianchen; Zhu, Ruilin; Zhang, Jing; Zhang, Yadi; Gu, Xiaopeng; Wu, Zihui; Yang, Liu (Frontiers in Nutrition, 2025)
BackgroundRetinopathy, a microvascular complication linked to obesity and metabolic dysfunction, is characterized by the absence of reliable anthropometric predictors. The weight-adjusted waist index (WWI), incorporating waist circumference and weight, may better capture visceral adiposity and its pathological impact. This study investigates the association between WWI and retinopathy in U.S. adults and explores the potential mediating role of glycated hemoglobin (HbA1c).MethodsA cross-sectional analysis was conducted on 5,572 adults aged ≥40 years from the 2005–2008 National Health and Nutrition Examination Survey (NHANES), in which retinopathy was assessed using retinal imaging. Multivariate logistic regression, restricted cubic spline models, subgroup analyses, and threshold effect analysis were used to evaluate the WWI-retinopathy relationship. Receiver operating characteristic curves (ROC) were employed to compare the predictive ability of WWI to other obesity indices. Mediation analysis assessed the role of HbA1c.ResultsOf 5,572 participants, 683 had retinopathy. Each unit increase in WWI was associated with a 31% higher risk of retinopathy (OR = 1.31, 95% CI: 1.16–1.48), increasing to 87% (OR = 1.87) in the highest quintile. WWI showed a dose-response relationship with retinopathy severity and consistent associations across subgroups. WWI outperformed weight, body mass index (BMI), and abdominal body shape index (ABSI) in predicting retinopathy (P < 0.05). Mediation analysis revealed that 30.02% of the WWI-retinopathy association was mediated by HbA1c (P < 0.001).ConclusionWWI serves as a stronger predictor of retinopathy than conventional obesity measures. The partial mediation by HbA1c highlights the interconnected roles of visceral fat and hyperglycemia in retinal microvascular damage.